Etiological factor of ascites and its correlation with serum ascites albumin gradient and cholesterol gradient in patients admitted at rural area - Porwal, Vinod; Porwal, Ashwin; Verma, Anand (International Journal of Advances in Medicine, 2016)
Background: The etiological spectrum of ascites is vast and practically includes pathology of all the systems. In most cases ascites will appear as a part of a well-recognized illness i.e. cirrhosis, tuberculosis, congestive heart failure, nephrosis or disseminated carcinomatosis. Few patients have more than one cause of ascites formation. Majority of cases of ascites are due to portal hypertension, mainly as a result of cirrhosis. Other subset of cause includes pathology of peritoneum, which are not related to portal hypertension. A portal hypertension ascites was distinguished from the non-portal hypertension causes by determining whether the fluid is transudate or exudate. But many infected and malignancy related samples have been reported to have transudative fluid and many samples obtained from patients with cirrhosis or heart failure had exudative ascitic fluid. Hence there is a need for this study to know the efficacy of serum ascites albumin gradient and serum ascites cholesterol gradient to differentiate ascites of portal and non-portal hypertensive etiology. Ascites associated with portal hypertension has high serum - ascites albumin gradient i.e ≥1.1 gm/dl, whereas ascites associated with peritoneal inflammation or malignancy has low gradient <1.1gm/dl. Methods: In this study 130 patients of ascites proved by ultrasound were included. They were studied using two parameters – serum ascites albumin gradient (SAAG) and serum ascites cholesterol gradient (SACG). Serum albumin, ascitic fluid albumin, serum cholesterol and ascitic fluid cholesterol was done in all patients. Results: SAAG was in portal hypertensive range in 96 of the 99 patients with portal hypertension and in non-portal hypertensive range in 24 of the 26 patients in non-portal hypertension causes. SAAG has efficacy of 96.15% in classifying ascites of portal hypertension and non-portal hypertension causes. Conclusions: The Mean±SD of SAAG in portal hypertension is 1.423±0.188 and in non-portal hypertension is 0.725±0.189 and is statistically significant in classifying ascites of portal and non-portal hypertension causes. A SAAG >1.1 gm/dl is suggestive of portal hypertension not only in patients with transudative type of ascites but also in cases with high protein concentration. The Mean±SD of SACG in malignant ascites is 38.2±10.8 and in non-malignant ascites is 78.1±20.2 and is statistically significant in classifying ascites into malignant and non-malignant etiology.